Gender Equality within Family in Islamic Perspective: Insights from The Hadiths of Ummul Mukminin - Nadia, Zunly; Faoziah, Niswatin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
The concept of gender equality is crucial in reinforcing societal foundations and addressing issues of injustice. This study emphasizes the importance of understanding gender equality within the context of families, recognized as one of society'smost influential institutions. By exploring gender dynamics within the family, this research draws on the Hadith, which encapsulates historical records and narratives from the Prophet Muhammad's life in a patriarchal Arab society. Despite societal norms, the Prophet’s Hadith texts, driven by principles of equality and justice, advocate for equal relationships between men and women, sparking considerable debate and protest from his contemporaries. The significance of Hadith texts from Ummul Mukminin (the Mothers of the Believers) in discussing gender relations within the family lies in their potential to serve as a reference source. Utilizing content analysis as a methodology, this research provides a comprehensive examination of relevant Hadiths and their implications for modern gender equality within the family. The findings highlight the Prophet’s dedication to creating a model of marital relations based on mutual respect, compassion, and equality. The study positions these texts as guides for families, helping them reinforce their functions and internalize equality values, contributing to the formation of a maslahah family—a family governed by principles prioritizing societal well-being.